2018
DOI: 10.1016/j.vaccine.2018.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for increasing uptake of vaccination in pregnancy in high-income countries: A systematic review

Abstract: Twenty-two articles were included in the review. The majority of the papers included were conducted in the USA and looked at strategies to increase influenza vaccination in pregnancy. There is limited high quality evidence for strategies in high-income countries to increase coverage of pertussis and influenza vaccination in pregnancy. A number of strategies have been found to be effective; reminders about vaccination on antenatal healthcare records, midwives providing vaccination, and education and information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 37 publications
3
76
0
Order By: Relevance
“…We also found that survivors' health care providers and family/friends were influential in FC uptake. This is consistent with studies of other health decisions where patients experience barriers, such as vaccination, where health care provider recommendations are persuasive in changing behavior . It also reinforces the importance of continued efforts to educate health care providers in an effort to improve patient‐provider communication about fertility and referral to fertility specialists .…”
Section: Discussionsupporting
confidence: 83%
“…We also found that survivors' health care providers and family/friends were influential in FC uptake. This is consistent with studies of other health decisions where patients experience barriers, such as vaccination, where health care provider recommendations are persuasive in changing behavior . It also reinforces the importance of continued efforts to educate health care providers in an effort to improve patient‐provider communication about fertility and referral to fertility specialists .…”
Section: Discussionsupporting
confidence: 83%
“…Achieving vaccine acceptance amongst pregnant women and maternity healthcare professionals (HCPs) has proven to be a considerable public health challenge, particularly in developed countries, and uptake of routine vaccination (especially influenza) remains suboptimal 15 . Furthermore, recruitment of pregnant women into clinical trials may be difficult, particularly as historically they have been excluded from participation, and there is a paucity of information regarding their recruitment and retention 16 17 .…”
Section: Introductionmentioning
confidence: 99%
“…RSV vaccines are likely to be available (for pregnant women) before the other new vaccines in the pipeline described above. Given the uptake of vaccines during pregnancy remains suboptimal in many countries, inclusion of a third vaccine will not be without challenges. Similarly, improving the uptake and timeliness of currently available vaccines for infants, children and adults either at high risk of bronchiectasis or those with existing disease should be a priority.…”
Section: Resultsmentioning
confidence: 99%